Functional Implications of Neurotransmitter Segregation - Cifuentes, Fredy; Morales, Miguel Angel (Frontiers in Neural Circuits, 2021)
Here, we present and discuss the characteristics and properties of neurotransmitter segregation, a subtype of neurotransmitter cotransmission. We review early evidence of segregation and discuss its properties, such as plasticity, while placing special emphasis on its probable functional implications, either in the central nervous system (CNS) or the autonomic nervous system. Neurotransmitter segregation is a process by which neurons separately route transmitters to independent and distant or to neighbouring neuronal processes; it is a plastic phenomenon that changes according to synaptic transmission requirements and is regulated by target-derived signals. Distant neurotransmitter segregation in the CNS has been shown to be related to an autocrine/paracrine function of some neurotransmitters. In retinal amacrine cells, segregation of acetylcholine (ACh) and GABA, and glycine and glutamate to neighbouring terminals has been related to the regulation of the firing rate of direction-selective ganglion cells. In the rat superior cervical ganglion, segregation of ACh and GABA to neighbouring varicosities shows a heterogeneous regional distribution, which is correlated to a similar regional distribution in transmission strength. We propose that greater segregation of ACh and GABA produces less GABAergic inhibition, strengthening ganglionic transmission. Segregation of ACh and GABA varies in different physiopathological conditions; specifically, segregation increases in acute sympathetic hyperactivity that occurs in cold stress, does not vary in chronic hyperactivity that occurs in hypertension, and rises in early ages of normotensive and hypertensive rats. Given this, we propose that variations in the extent of transmitter segregation may contribute to the alteration of neural activity that occurs in some physiopathological conditions and with age.